Computational insights into the inhibitory mechanism of type 2 diabetes mellitus by bioactive components of Oryza sativa L. indica (black rice) - Rasool, Kashaf; Bhatti, Attya; Satti, Abid Majeed; Paracha, Rehan Zafar; John, Peter (Frontiers in Pharmacology, 2024)
Background: Type 2 Diabetes Mellitus is metabolic disease and is categorized by hyperglycemia, resistance to insulin and ß-cell dysfunction. Around the globe, about 422 million people have diabetes and out of which 1.5 million die annually. In spite of innovative advancements in field of diabetes, no biological drug has been known to successfully cure and avert its progression.Thereupon, natural drugs derived from plants are emerging as novel therapeutic strategy to combat diseases like diabetes.Objective: Current study aims to investigate antidiabetic potential of natural compounds of Oryza sativa L. indica (black rice) in disease treatment.Methods: Anti-oxidant activity and alpha amylase assays were performed to evaluate therapeutic potential of the extract. Gas Chromatography-Mass Spectrometry (GC-MS) was used for identification of constituents from the ethanol extract. ADMET profiling (absorption, distribution, metabolism, excretion and toxicity), network pharmacology and molecular dynamics simulation were employed in order to uncover the active ingredients and their therapeutic targets in Oryza sativa L. indica against type 2 diabetes mellitus.Results: GC-MS of plant extract provided total list of 184 compounds. Lipinski filter and toxicity parameters screened out 18 compounds. The topological parameter of Protein-Protein Interaction (PPI) were used to shortlist the 9 key proteins (STAT3, HSP90AA1, AKT1, SRC, ESR1, MAPK1, NFKB1, EP300, and CREBBP) in the type 2 diabetes mellitus pathways. Later, molecular docking analysis and simulations has shown that C14 (1H-Purine-8-propanoic acid, .alpha.-amino-2, 3, 6, 7-tetrahydro-1,3,7-trimethyl-2,6-dioxo-) and C18 (Cyclohexane-carboxamide, N-furfuryl) bind with AKT1 and ESR1 with binding energy of 8.1, 6.9, 7.3 and 7.2 kcal/mol, respectively. RMSD (root mean square deviation) and RMSF (root mean square fluctuation) values for AKT1 and ESR1 has shown very little fluctuation, it indicated that proteins were stabilized after ligand docking.The study shows therapeutic drug candidates against AKT1 and ESR1 to treat type 2 diabetes mellitus. However, further wet-lab analysis is required to find out the best remedy for type 2 diabetes mellitus.